MENANAMKAN NILAI KEARIFAN LOKAL MASYARAKAT SUNDA KEPADA ANAK-ANAK “Kinderdorf” LEMBANG - Dian Indira,; R M Mulyadi,; Hilman Fauzia, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Society develops dynamically in accordance with the times, as is the case in West Java, which currently has a heterogeneous society. Living in a heterogeneous environment requires speaking in a language that is equally understood between speakers, so it cannot be denied that the possibility of shifting Sundanese culture/language as the language of the Sundanese people cannot be denied. Children are the hope for the preservation of Sundanese language and culture, so that the Sundanese language/culture can continue to be inherited. Community service activities (PKM) carried out in "Kinderdorf" - Lembang with the theme "Instilling the Value of Local Wisdom in Children Through Reading Folklore", aims to introduce Sundanese culture to children in "Kinderdorf" and instill local wisdom in children -children through reading in the form of Sundanese folk stories and martial arts. The method used in the form of counseling the importance of local wisdom and simple Sundanese language training. The results obtained are that although the students live in an environment that communicates using Sundanese, most of the students there cannot speak Sundanese. The activities carried out have a positive impact on students, this can be seen by the enthusiasm shown when learning Sundanese interactively indirectly through silat gymnastics activities. The students can follow the instructions given by the trainer in Sundanese for every movement made